A análise da constitucionalidade da prescrição do redirecionamento por dissolução irregular na execução fiscal - Braz, Lucas Miranda Lucena (2016)
The present work seeks to analize the current pattern related to the transfer of the fiscal responsibility to the individual administrator of a company throughout the process of fiscal execution, verifying the possibility to alegate, within the execution procedure, the prescription of the right, or the limitation period of action for the Fiscal Administration, in respect to restrainig fundamental constitucional principles, observing the existence of inertia on the actions of fiscal suing organs on requesting for the implementation of the mesure. To achieve the objective, the paper pursues the analysis of constitucional principles such as Juridical Security, Reasonabilitiy and Proportionality, building parallels, in order to obtain a positioning compatible with the text of the Federal Constitution, questioning whether or not is necessary to delimitate the usage of the executed mesure, otherwise fundamental rights would be affronted. To the comprehension of the presented thesis, this study develops concepts and drafts arguments to support the expressed idea. Citing notorious doctrine about the studied subject, the research seeks to develop, critically, an evaluation about the usage of the transfer of the fiscal responsibility to the individual administrator within the process of Fiscal Execution, elaborating critics regarding the way which the fiscal transfer of responsability has been implemented, proposing a new preveiw of the matter under the guidance of constitucional interpretation, without deviating of the treatment applied on the subject by judicial decisions, notedly decisions pronounced by the Supreme Court of Justice.